La comunicación no convencional en los clubes de fútbol - Olabe Sánchez, Fernando (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2010)
Corporate image management in Spanish football clubs has received a boost in the last decade thanks to the integration of Communication Departments into the organisational structure of the clubs, in many cases as a complement to marketing departments, and, in others, as departments in themselves combining all aspects of communication. Football clubs no longer deal only with the media as transmitters of their corporate identity and business management. Club image is now increasingly directed at club members, supporters’ clubs, executives, fans in general and other public and private organisations. The aim of this study is to describe the communicative operations of these sporting organisations in the two categories of the Spanish Professional Football League. To this end, the research has been carried out by survey method, allowing the analysis of communicative tools, operations and strategies employed by PR departments in the management of Communication in the football clubs. The research shows that the 42 clubs of the Spanish Professional Football League continue, in the majority, to rely on a model of public relations that prizes publicity. Although having committed themselves to the professionalization of their corporate image management and having created departments for this specific purpose, there is still a widespread rejection, either because of lack of resources or ignorance, of other operations which would permit an integrated communication management.